Improving the quality of seed populations Nigella sativa L. with the combination of sulfur and biological compounds in calcareous soil under drought stress conditions - Reza Taherdoost; Mahmood Dejam; Mehdi Madandoust; Farhad Mohajeri (علوم و فناوری بذر ایران, 2025)
The use of sulfur (S) is of special interest in arid and semi-arid Iran since most soils are calcareous. In order to improve germination, seedling growth, and quality of Nigella sativa L. seeds obtained from mother plants grown under drought stress conditions, this investigation was performed in split plots with a completely randomized block design with three replications in research farm Fasa City in 2022. The main factor was irrigation after 25, 50 and 75 percent of soil moisture depletion and the subplots were fertilizer in 8 levels including 100 % S, 50% S + thiobacillus, 50% S + mycorrhiza, 50% S+ thiobacillus+ mycorrhiza, thiobacillus, mycorrhiza, thiobacillus+ mycorrhiza and control. The results showed that in irrigation with 75 percent soil moisture depletion, the integration of 50% S+ thiobacillus+ mycorrhiza decreased the seed membrane stability by 23 percent compared to the control. In an irrigation regime with 75 percent moisture depletion, the integration of 50% S+ thiobacillus+ mycorrhiza and 50% S+ mycorrhiza caused a 31 percent increase in amylase activity in seeds endosperm about control. The highest germination percent and rate are also observed in the integration of 50% S+ thiobacillus+ mycorrhiza. Moreover in the treatment with 75 percent soil moisture depletion, the 50% S+ thiobacillus+ mycorrhiza increased the seed vigor to 46 percent. With regards to the positive effects of sulfur integration with Thiobacillus and mycorrhiza in the improvement of the quality of seeds derived from black cumin under drought stress, the use of these biological compounds should be recommended.